Hemispheric relations in the 21st century. - TULCHIN, Joseph S. (1997)
Argues that Latin American leaders are ambivalent about the nature of US hegemony and its effect on the national interests of their countries. Notes that US preoccupation with Europe means that Latin America can exercise considerable autonomy in defining its own role in world affairs, and contribute, in a meaningful and substantial fashion, to the shaping of the hemispheric community.